Consequences of COVID-19 on Iran’s economy and sports industry: Analysis and improvement strategies - Kiani, Mohammad Saeid; Nazari, Leila (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to analyze the effects of COVID-19 on Iran’s economy and sports industry and to provide solutions to compensate for these losses. The present study was descriptive-survey in terms of its practical purpose and the method of data collection. In the first (qualitative) phase, 24 interviews were conducted with economics experts and sports economics faculty nationwide. In the second (quantitative) phase, 610 questionnaires were distributed and analyzed—both in person and online—among postgraduate sports management students across the country. The results showed that the spread of the COVID-19 virus did not have only negative effects and it also had many positive effects on the sports industry. The sports industry can have a very high capacity to adapt to the crisis of the spread of COVID-19 and similar crises. Holding classes and workshops in various sports fields and sports sciences online, paying more attention to family sports, sports at home and open spaces and in the economic sector, during the period of the COVID-19 epidemic, online sports businesses flourished and the managers of sports complexes found financial alternatives. Overall, the negative effects of the COVID-19 pandemic, especially the economic ones, were more significant than the positives for sports, mainly due to its sudden onset, rapid spread, and the sports industry’s lack of preparedness.